2019
DOI: 10.1002/lom3.10300
|View full text |Cite
|
Sign up to set email alerts
|

An international intercomparison of stable carbon isotope composition measurements of dissolved inorganic carbon in seawater

Abstract: We report results of an intercomparison of stable carbon isotope ratio measurements in seawater dissolved inorganic carbon (δ13C‐DIC) which involved 16 participating laboratories from various parts of the world. The intercomparison involved distribution of samples of a Certified Reference Material for seawater DIC concentration and alkalinity and a preserved sample of deep seawater collected at 4000 m in the northeastern Atlantic Ocean. The between‐lab standard deviation of reported uncorrected values measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…At NTU, final δ 13 C values were obtained after instrumental drift correction, blank correction for standards (Assayag et al, 2006;Humphreys et al, 2016), and calibration using NBS-18 (δ 13 C = −5.01‰) and Estremoz (δ 13 C = 1.63‰) calcium carbonate standards. All δ 13 C values of the samples were further corrected by accounting for the difference between the international consensus value of δ 13 C DIC of the Dickson CRM (0.78‰) (Cheng et al, 2019) and our laboratory measurements of δ 13 C DIC of the Dickson CRM at NTU (the magnitude of this correction was mostly below 0.4‰). The standard deviation for δ 13 C of DIC measurements over multiple years at UC Davis is reported as ±0.1‰ (https://stableisotopefacility.ucdavis.edu/) and at NTU was ±0.2‰ (Carrara marble, n = 24, 4 runs).…”
Section: Sample Analysismentioning
confidence: 99%
“…At NTU, final δ 13 C values were obtained after instrumental drift correction, blank correction for standards (Assayag et al, 2006;Humphreys et al, 2016), and calibration using NBS-18 (δ 13 C = −5.01‰) and Estremoz (δ 13 C = 1.63‰) calcium carbonate standards. All δ 13 C values of the samples were further corrected by accounting for the difference between the international consensus value of δ 13 C DIC of the Dickson CRM (0.78‰) (Cheng et al, 2019) and our laboratory measurements of δ 13 C DIC of the Dickson CRM at NTU (the magnitude of this correction was mostly below 0.4‰). The standard deviation for δ 13 C of DIC measurements over multiple years at UC Davis is reported as ±0.1‰ (https://stableisotopefacility.ucdavis.edu/) and at NTU was ±0.2‰ (Carrara marble, n = 24, 4 runs).…”
Section: Sample Analysismentioning
confidence: 99%
“…Various factors were identified as the causes of these discrepancies: sample homogeneity, reference materials, synthetic samples, alteration during storage and transportation, etc. Recently, Cheng et al reported consistent results of an international intercomparison for the δ 13 C DIC value of seawater.…”
Section: Introductionmentioning
confidence: 64%
“…Overall, unlike an open and evolved modern ocean with δ 13 C ranging from -6.56 to +3.10‰ (Cheng et al, 2019), δ 18 O ranging from -1.5 to +1.8‰ (Carpenter and Lohmann, 1995) and positive Zn isotope composition (δ 66 Zn = +0.34‰; John et al, 2005) the ocean at "embryonic" stage has heavy both C and O isotope composition (δ 13 C > 6‰, δ 18 O > 4‰; Table 7) and negative Zn isotope composition (δ 66 Zn average = -0.06‰). Calcium isotope compositions of both types of ocean are similarly heavy: δ 44 Ca open evolved ocean = 1.92‰ (Fantle and Tipper, 2014), δ 44 Ca "embryonic" ocean = 1.22-1.64‰ (Table 7).…”
Section: Chemistry Of the End-member Hydrothermal Fluidmentioning
confidence: 96%